2019
DOI: 10.1088/1748-9326/ab51be
|View full text |Cite
|
Sign up to set email alerts
|

Cross-scale interactions of socio-hydrological subsystems: examining the frontier of common pool resource governance in Arizona

Abstract: A critical frontier of water management in the western US is the challenge of cross-scale interactions. It is difficult to establish clear governance boundaries and collectively act when basins are interconnected, surface water and groundwater flows are interrelated, and urban and rural water demands are increasingly affected by regional and international telecoupling. Changing climate, snowpack, and rainfall, peri-urbanization, and shifting economics of rural landscapes further increase sustainable governance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…A socio-behavioral measure considered to have greater top-down determination is policy preference, choice, action, or intention. In fact, 21% of the studies included variables representing a socio-behavioral dimension including policies or a policy (Liu et al, 2015;Srinivasan, 2015;Di Baldassarre et al, 2016;Garcia and You, 2016;Giuliani et al, 2016;Grames et al, 2016;Bakarji et al, 2017;Farjad et al, 2017;Gonzales and Ajami, 2017;Haeffner et al, 2017;Han et al, 2017;Khan et al, 2017;Kotir et al, 2017;Noël and Cai, 2017;Re et al, 2017;Sanderson et al, 2017;Essenfelder et al, 2018;Keys and Wang-Erlandsson, 2018;Robinne et al, 2018;Abebe et al, 2019a,b;York et al, 2019;Bradford et al, 2020;Du et al, 2020;Wilfong and Pavao-Zuckerman, 2020;Bou Nassar et al, 2021;Hanus, 2021;Oneda and Barros, 2021;Savelli et al, 2021;ZamanZad-Ghavidel et al, 2021).…”
Section: Social Components Used In Primary Studiesmentioning
confidence: 99%
“…A socio-behavioral measure considered to have greater top-down determination is policy preference, choice, action, or intention. In fact, 21% of the studies included variables representing a socio-behavioral dimension including policies or a policy (Liu et al, 2015;Srinivasan, 2015;Di Baldassarre et al, 2016;Garcia and You, 2016;Giuliani et al, 2016;Grames et al, 2016;Bakarji et al, 2017;Farjad et al, 2017;Gonzales and Ajami, 2017;Haeffner et al, 2017;Han et al, 2017;Khan et al, 2017;Kotir et al, 2017;Noël and Cai, 2017;Re et al, 2017;Sanderson et al, 2017;Essenfelder et al, 2018;Keys and Wang-Erlandsson, 2018;Robinne et al, 2018;Abebe et al, 2019a,b;York et al, 2019;Bradford et al, 2020;Du et al, 2020;Wilfong and Pavao-Zuckerman, 2020;Bou Nassar et al, 2021;Hanus, 2021;Oneda and Barros, 2021;Savelli et al, 2021;ZamanZad-Ghavidel et al, 2021).…”
Section: Social Components Used In Primary Studiesmentioning
confidence: 99%
“…Therefore, recognizing the interactions across scales is fundamental for improving future projections, particularly in systems dominated by changing social dynamics (Srinivasan et al, 2017;York et al, 2019). Although no cross-scale studies were identified in our review, cross-scale analyses exist for applications other than natural hazards, including water resources management (York et al, 2019). We observed an overreliance on local case studies that ignore broad socio-political contexts, and vice versa.…”
Section: Research Agendamentioning
confidence: 96%
“…This is required as the dynamic interactions between natural hazards and society share nonlinear behaviours that are driven by forces interacting across spatial and temporal scales (Adger et al, 2005;Birkmann and von Teichman, 2010;Nelson et al, 2006;Peters et al, 2004;Räsänen, 2021;Vanelli and Kobiyama, 2021). Therefore, recognizing the interactions across scales is fundamental for improving future projections, particularly in systems dominated by changing social dynamics (Srinivasan et al, 2017;York et al, 2019). Although no cross-scale studies were identified in our review, cross-scale analyses exist for applications other than natural hazards, including water resources management (York et al, 2019).…”
Section: Research Agendamentioning
confidence: 99%
“…Each of the above cases shows a deepening grasp by scientists and decision-makers that understanding cross-scale interactions are critical to both comprehending complex socio-ecological systems and to crafting solutions to such problems [23,24]. This is not a new insight and, indeed, some of the earliest theories of managing the commons acknowledged the impact of the interaction of higher jurisdictions (such as national governments or international bodies like the United Nations) on the provision of collective public goods through the actions of individuals and households [25,26].…”
Section: Knowledge and Action Across Scalesmentioning
confidence: 99%